2018
DOI: 10.36076/ppj.2018.5.e501
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 3 Approaches to Percutaneous Epidural Adhesiolysis and Neuroplasty in Post Lumbar Surgery Syndrome

Abstract: Background: Percutaneous epidural adhesiolysis and neuroplasty (PEAN) has been proven to be safe and effective in treating different spine pathologies, in particular post lumbar surgery syndrome (PLSS). Objectives: The purpose of this study was to compare the efficacy and complication rates of the 3 different PEAN anatomical approaches (caudal, S1 foraminal, and L5-S1 transforaminal) used to treat PLSS. Study Design: This study used a case control, blind study. Setting: The research took place at the pain clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…In a study by Salem et al, no significant difference was found among these 3 approaches in reducing pain and improving function in patients with post-lumbar surgery syndrome. [4,13] Recently, a contralateral interlaminar retrograde approach has been introduced. [5] When performing PEA via a transforaminal approach, 2 options are available: an approach through the safe triangle and an approach through the retrodiscal space.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In a study by Salem et al, no significant difference was found among these 3 approaches in reducing pain and improving function in patients with post-lumbar surgery syndrome. [4,13] Recently, a contralateral interlaminar retrograde approach has been introduced. [5] When performing PEA via a transforaminal approach, 2 options are available: an approach through the safe triangle and an approach through the retrodiscal space.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Salem et al, no significant difference was found among these 3 approaches in reducing pain and improving function in patients with post-lumbar surgery syndrome. [ 4 , 13 ] Recently, a contralateral interlaminar retrograde approach has been introduced. [ 5 ]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations